2022
DOI: 10.3390/atmos13010145
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling of RPCA-FCM in Spatiotemporal Rainfall Patterns Recognition

Abstract: This study was conducted to identify the spatiotemporal torrential rainfall patterns of the East Coast of Peninsular Malaysia, as it is the region most affected by the torrential rainfall of the Northeast Monsoon season. Dimension reduction, such as the classical Principal Components Analysis (PCA) coupled with the clustering approach, is often applied to reduce the dimension of the data while simultaneously performing cluster partitions. However, the classical PCA is highly insensitive to outliers, as it assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Mariana S et al [8] proposed a statistical modeling of torrential rainfall pattern recognition to alleviate the drawback of PCA (highly insensitive to outliers, as it assigns equal weights to each set of observations) and the traditional clustering algorithms which only allowed each element to exclusively belong to one cluster. [8] also introduced a robust PCA (RPCA) based on Turkey's biweight correlation and identified the optimum breakdown point to extract the number of components. A breakdown point of 0.4 at 85% cumulative variance was identified to efficiently extract the number of components to avoid low-frequency variations or insignificant clusters on a spatial scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mariana S et al [8] proposed a statistical modeling of torrential rainfall pattern recognition to alleviate the drawback of PCA (highly insensitive to outliers, as it assigns equal weights to each set of observations) and the traditional clustering algorithms which only allowed each element to exclusively belong to one cluster. [8] also introduced a robust PCA (RPCA) based on Turkey's biweight correlation and identified the optimum breakdown point to extract the number of components. A breakdown point of 0.4 at 85% cumulative variance was identified to efficiently extract the number of components to avoid low-frequency variations or insignificant clusters on a spatial scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important aspect of FCM is using the Euclidean distance, which is based on a criterion of the distance between samples. Unlike other clustering methods, the FCM method allows data to belong to more than one cluster (Che Mat Nor et al, 2022).…”
Section: 83fuzzy C-means Algorithmmentioning
confidence: 99%
“…Precipitation can regulate the ecosystems that a population depends on, and it has far-reaching effects on socioeconomical sustainability and the security of increasingly scarce water resources [9]. Many previous studies on precipitation patterns [10][11][12][13] have shown that precipitation fluctuates across regions, and they have proved the importance of precipitation spatiotemporal patterns in the prediction of future climate change [14]. Therefore, understanding precipitation change in different regions is crucial for the identification of regional changes in climate and the mitigation of the resultant impacts.…”
Section: Introductionmentioning
confidence: 99%